Protonation‐Driven Membrane Insertion of a pH‐Low Insertion Peptide. Issue 40 (31st August 2016) - Hanz, Samuel Z.; Shu, Nicolas S.; Qian, Jieni; Christman, Nathaniel; Kranz, Patrick; An, Ming; Grewer, Christof; Qiang, Wei
Abstract: The pH‐low insertion peptide (pHLIP) inserts into membranes and forms a transmembrane (TM) α‐helix in response to slight acidity, and has shown great potential for cancer diagnosis and treatment. As a lead, pHLIP is challenging to optimize because the mechanism of its pH‐dependent membrane interactions is not completely understood. Within pHLIP there are multiple D/E residues which could sense the pH change, the particular role played by each of them in the protonation‐driven insertion process is not clear. The precise location of the TM helix within the pHLIP sequence is also unknown. In this work, solid‐state NMR spectroscopy is used to address these central questions. Tracing backbone conformations revealed that the TM helix spans from A10 to D33 with a break at T19 to P20. Residue‐specific p K a values of D31, D33, D25, and D14 were determined to be 6.5, 6.3, 6.1, and 5.8, respectively, and define the sequence of protonations which lead to insertion. Furthermore, possible intermediate states which disrupt membranes at pH 6.4 were proposed based on tryptophan fluorescence quenching and NMR data. Abstract : Showing backbone : The pH‐low insertion peptide (pHLIP) inserts into membranes and forms a transmembrane (TM) α‐helix in response to acidity changes. Tracing backbone conformations revealed that the TM helix spans from A10 to D33 with a break at T19 to P20. Residue‐specific p K a values of D31, D33, D25, and D14 were determined to be 6.5, 6.3, 6.1, and 5.8, respectively, and define the sequence of protonations which lead to insertion. Furthermore, possible intermediate states which disrupt membranes at pH 6.4 are proposed.